Peran Posyandu dalam Meningkatkan Kesehatan Balita di Lingkungan VI Pajak Rambai - Larasati Arum Utami; Tariza Fairuz; Stefany Hotnida Napitupulu; Keyla Dahlia Manihuruk; Malikah Sofia Rahman Nainggolan (IAI Nasional Laa Roiba Bogor, 2026)
Posyandu (Integrated Service Post) is a form of Community-Based Health Effort (UKBM) that plays a vital role in improving the health of children and mothers. In Neighborhood VI Pajak Rambai, Posyandu functions as a center for monitoring toddlers' growth and development, providing immunizations, nutrition counseling, and supplementary feeding (PMT). This study uses a qualitative approach with data collection methods including direct observation, semi-structured interviews with cadres and parents of toddlers, as well as documentation of attendance records and child growth charts. Data analysis was conducted thematically and descriptively, with triangulation to ensure the validity and reliability of the results. The findings indicate that Posyandu regularly provides weighing and height measurement services, immunizations, nutrition counseling, PMT, and education on healthy parenting and child hygiene to parents. Active parental participation is a key factor supporting the success of the program. Routine monitoring shows significant improvements in toddlers' weight and height over time. Additionally, Posyandu serves as a health information center that increases parental awareness of maintaining family health. Overall, Posyandu in Neighborhood VI Pajak Rambai has a strategic role in supporting the healthy growth and development of toddlers through integrated health services and community education.